Group B streptococcal immunisation of pregnant women for the prevention of early and late onset Group B streptococcal infection of the neonate as well as adult disease - Anna L. Kenchington; Ronald F. Lamont (Taylor & Francis Group, 2017)
Introduction: Early onset neonatal Group B streptococcal disease is preventable. Intrapartum antibiotic prophylaxis has resulted in a significant reduction in neonatal mortality and morbidity. National guidelines for the selection of women eligible for intrapartum antibiotic prophylaxis, whether screening-based or risk-based, differ according to the local burden of disease. Despite the introduction of intrapartum antibiotic prophylaxis, there remains a significant burden of disease, which can be resolved by better adherence to guidelines, rapid identification of maternal colonization or in the future, vaccination. Areas covered: The introduction of a vaccine to women in the third trimester is likely to further reduce the burden of disease and provide benefits beyond the prevention of early neonatal disease, including meningitis and disability following late onset disease. Development of specific polyvalent vaccines continues, but testing has challenges and may require surrogate markers or molecular-based techniques to manipulate antigenicity and immunogenicity. Expert commentary: Group B streptococcal vaccination using conjugated polyvalent vaccines against the major disease causing serotypes of Group B streptococcus, either alone, or in combination with a policy of intrapartum antibiotic prophylaxis, may decrease the burden of Group B streptococcus beyond that achieved by current use of intrapartum antibiotic prophylaxis alone.